(untitled) (Fiep Bulletin - online, 2016)
The increase in sedentary lifestyle worldwide and Brazil have contributed to the increase in chronic degenerative processes such as heart disease, diabetes and cancer. The aim of this research was to determine the prevalence of physical inactivity and relate the level of sedentary lifestyle and nutritional status of schoolchildren from the High School of State Public Network municipality of Piripiri-PI. The study was cross-sectional, descriptive, which were evaluated 210 schoolchildren of both sexes, with average age of 15.5 ± 1.1, enrolled in the public network State concoction-PI school. For data collection was carried out anthropometric measurements and questionnaires to identify the level of physical activity. The statistical analysis was applied to descriptive statistics with average procedures ± standard deviation for sample characterization and Chi - square test for association between sex and all variables and level of physical activity and nutritional status (p <0.05) . The prevalence of physical inactivity was 78.5% for both sexes. Boys had become more active (31.0%), compared with girls (12.1%). Regarding nutritional status (BMI), most school 73.80% was classified in ideal weight. There was a significant association only in very sedentary category, between sex and level of physical activity (p <0.05). The prevalence of physical inactivity (78.5%) of school of chilli-PI was considered high, with higher prevalence in women. There was a significant association only in very sedentary category, between sex and level of physical activity (p <0.05). There was no significant association between a sedentary lifestyle and nutritional status.